Exploring the impact of partial sand replacement with olive waste on mechanical and thermal properties of sustainable concrete - EL Boukhari, Mohamed; Merroun, Ossama; Maalouf, Chadi; Bogard, Fabien; Kissi, Benaissa (Cleaner Materials, 2023)
This paper presents the results of a study conducted to develop structural concrete with reduced thermal conductivity, using organic by-products such as Olive Waste (OW) as a lightweight aggregate. Different concrete specimens were elaborated by using two different types of OW and by replacing an equal volume of sand. The first one involved Olive Pomace solid aggregates (OP) while the second type is Olive Pomace solid aggregates immersed in Olive Mill Wastewater (OPWW). For each type, two series of concrete were produced using OW in both dry and saturated states. The percentage of natural sand substitution by OW ranged from 0% to 15%. The main objective of this study is to experimentally determine whether the mechanical properties and thermal conductivity of the elaborated specimens could be improved compared to the reference concrete. The mechanical tests indicated that the concrete specimens containing 5% of OPWW in dry state recorded the best mechanical performance compared to the reference concrete. The incorporation of OW also enhances the thermal conductivity of the concrete specimens. Furthermore, the thermal conductivity of this concrete specimen decreased from 1.3 W/m.K for control concrete to 0.86 W/m.K.
Keywords: Eco-friendly construction materials; Lightweight construction solutions; Low-density concrete; Olive waste; Thermal conductivity and strength properties; Waste management